HEALTH AWARENESS PROFILE OF LATE ADOLESCENTS (16-16 YEARS) OF A RURAL AREA OF KANPUR - Verma, Santosh Kumar; Sharma, R P; Chandra, Suresh; Martollia, D S; Verma, Punit (Indian Journal of Community Health, 2008)
.